Spontaneous Adsorption of Graphene Oxide to Oil–Water and Air–Water Interfaces by Adsorption of Hydrotropes. Issue 9 (23rd March 2020) - Turpin, Geosmin A.; Holt, Stephen A.; Scofield, Joel M. P.; Teo, Boon M.; Tabor, Rico F.
Abstract: The interfacial adsorption of graphene oxide (GO) is crucial in phenomena such as emulsification and froth flotation, where presence of 2D nanomaterials facilitates Pickering stabilization. This process usually requires the input of high amounts of shear energy, or is aided by surfactants in order to make it possible at room temperature. In this work, a surfactant‐free method for interfacial enrichment through the use of a family of tetraalkylammonium hydrotropes, the most effective being tetraethylammonium chloride (TEAC), is demonstrated. As both GO and hydrotropes do not spontaneously enrich to interfaces on their own, this synergistic, spontaneous effect highlights that hydrotropes adsorb to GO sheets, decreasing their negative charge while rendering them more amphiphilic and therefore making it thermodynamically favorable for them to adsorb to the interface. Evidence for this adsorption includes increases in surface pressure, as well as emulsion and froth stability when both GO and hydrotropes are present in a system. Hydrotropes perform as well as or better than surfactants. Adsorption is irreversible, with XRR and AFM studies demonstrating that roughness increases with compression of the air‐water interface, showing that GO sheets are crumpling at the interface rather than desorbing, providing new routes to patterned and structured GO layers. Abstract : Hydrotropes (small organic solubilizing agents) are used to make graphene oxide spontaneously surface active through adsorption, enriching it at air/water and oil/water interfaces. In doing so, stable emulsions and foams are produced at low energy cost, offering new opportunities for formulation of nanomaterial‐stabilized soft systems.